Psychosocial Factors and Quality of Life of Portuguese Adolescents With Chronic Conditions – Increased Risk for Victims of Bullying - Ana Cerqueira; Fábio Botelho Guedes; Tania Gaspar; Emmanuelle Godeau; Celeste Simões; Margarida Gaspar de Matos (Continuity in Education, 2024)
The experience of living with a chronic condition (CC) impacts adolescents’ psychological and social adjustment and overall functioning. Considering the increased risk of psychosocial challenges among adolescents with CC, this study aimed to enhance our understanding of the psychological and social factors that impact their quality of life. It also compared the psychological and social variables among (a) adolescents with and without CC and (b) adolescents with CC who are and who are not victims of bullying. The results demonstrated that adolescents with CC showed more psychosocial difficulties than their peers, as they more frequently reported involvement in situations of violence, and demonstrated more difficulties at a psychological and emotional level. Further, being victims of bullying increased the psychosocial vulnerabilities of these adolescents. A better quality of life was associated with the following psychosocial factors: not being a victim of bullying or cyberbullying, having less anxiety and fewer depressive symptoms, liking school, receiving more support from family and friends, having better relationships with peers, and having fewer physical and psychological symptoms. These findings are significant for helping schools develop tools and strategies to address violence and support students with CC, who are at a higher risk of being involved in such situations and require a targeted response.